Participation, metaphysics, and enlightenment: reflections on Ken Wilber’s recent work - Ferrer, Jorge (Approaching Religion, 2015)
This article critically examines Ken Wilber’s (2006) recent work from a participatory perspective of human spirituality. After a brief introduction to the participatory approach, I limit my discussion to the following four key issues: a. the participatory critique of Wilber’s work, b. the cultural versus universal nature of Wilber’s Kosmic habits, c. the question of (post-)metaphysics in spiritual discourse, and d. the nature of enlightenment. The article concludes with some concrete directions in which to move the dialogue forward.